Grandfather and I - Buckley, Helen E. (New York : Scholastic Inc, 1994)
Mother and Father hurry. Brother and Sister hurry. But not Grandfather and I! We stop and look . . . just a s long as we like!
Keywords: Grandfathers--Fiction; Children stories